2011
DOI: 10.19173/irrodl.v12i6.991
|View full text |Cite
|
Sign up to set email alerts
|

Quality assurance in Asian distance education: Diverse approaches and common culture

Abstract: With the phenomenal expansion of distance education in Asia during the past three decades, there has been growing public demand for quality and accountability in distance education. This study investigates the national quality assurance systems for distance education at the higher education level in Asia with the aim of contributing to a better understanding of the current level of development of quality assurance in Asian distance education and to offer potential directions for policy makers when developing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 7 publications
1
17
0
7
Order By: Relevance
“…Επιπλέον, τα περισσότερα ιδρύματα επιδίωξαν -εκτός από την εθνική αναγνώριση μέσω πιστοποίησης-και τη διεθνή αναγνώριση, μέσω πιστοποίησης ISO όπως το πανεπιστήμιο Terbuka της Ινδονησίας. Από την πρόσφατη έρευνα των Jung et al (2011) για τα συστήματα διασφάλισης της ποιότητας στην τριτοβάθμια εξ αποστάσεως εκπαίδευση σε χώρες της ανατολικής, της νότιας και της νοτιοανατολικής Ασίας, (Κίνα, Ινδία, Ινδονησία, Ιαπωνία, Νότια Κορέα, Μαλαισία, Μογγολία, Φιλιππίνες, Σιγκαπούρη και Σρι Λάνκα) και το Χονγκ-Κονγκ, διαπιστώθηκε ότι οι ασιατικές χώρες έχουν υιοθετήσει τρεις προσεγγίσεις για τη διασφάλιση της ποιότητας στην εξ αποστάσεως εκπαίδευση. Στην πρώτη κατηγορία, όπως για παράδειγμα στο Χονγκ Κονγκ, στη Μαλαισία, στη Ινδονησία, στις Φιλιππίνες, στη Σιγκαπούρη και στη Σρι Λάνκα, η εξ αποστάσεως εκπαίδευση θεωρείται ως αναπόσπαστο τμήμα της τριτοβάθμιας εκπαίδευσης και έτσι εφαρμόζονται οι ίδιες διαδικασίες και τα ίδια κριτήρια για όλους τους τύπους των εκπαιδευτικών ιδρυμάτων.…”
Section: ανοικτότητα και ευελιξία σπουδών σημαίνει και χαμηλή ποιότητunclassified
“…Επιπλέον, τα περισσότερα ιδρύματα επιδίωξαν -εκτός από την εθνική αναγνώριση μέσω πιστοποίησης-και τη διεθνή αναγνώριση, μέσω πιστοποίησης ISO όπως το πανεπιστήμιο Terbuka της Ινδονησίας. Από την πρόσφατη έρευνα των Jung et al (2011) για τα συστήματα διασφάλισης της ποιότητας στην τριτοβάθμια εξ αποστάσεως εκπαίδευση σε χώρες της ανατολικής, της νότιας και της νοτιοανατολικής Ασίας, (Κίνα, Ινδία, Ινδονησία, Ιαπωνία, Νότια Κορέα, Μαλαισία, Μογγολία, Φιλιππίνες, Σιγκαπούρη και Σρι Λάνκα) και το Χονγκ-Κονγκ, διαπιστώθηκε ότι οι ασιατικές χώρες έχουν υιοθετήσει τρεις προσεγγίσεις για τη διασφάλιση της ποιότητας στην εξ αποστάσεως εκπαίδευση. Στην πρώτη κατηγορία, όπως για παράδειγμα στο Χονγκ Κονγκ, στη Μαλαισία, στη Ινδονησία, στις Φιλιππίνες, στη Σιγκαπούρη και στη Σρι Λάνκα, η εξ αποστάσεως εκπαίδευση θεωρείται ως αναπόσπαστο τμήμα της τριτοβάθμιας εκπαίδευσης και έτσι εφαρμόζονται οι ίδιες διαδικασίες και τα ίδια κριτήρια για όλους τους τύπους των εκπαιδευτικών ιδρυμάτων.…”
Section: ανοικτότητα και ευελιξία σπουδών σημαίνει και χαμηλή ποιότητunclassified
“…Based on the items confirmed by Jung (2011) andJung et al (2011), the initial 55 quality criteria across 10 quality dimensions were identified and refined to gain information about the learners' perceptions of DE quality. This initial list was then reviewed by five DE experts in Asia (India, Japan, Korea, Malaysia, and Thailand) regarding the relevancy and validity of the items for measuring DE quality.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…Among all the research topics, quality assurance of e-learning has attracted the greatest concern. Jung et al (2011) found that various national, regional, and international initiatives have been undertaken with regard to quality assurance in e-learning. Endean et al (2010) stated that those concerned about online learning have been developing and publishing ideas for over a decade about how to manage the quality of the learning experience of those trying to study through the Internet.…”
Section: Northrup P T (2002mentioning
confidence: 99%